1975
DOI: 10.1159/000459009
|View full text |Cite
|
Sign up to set email alerts
|

Biological Aspects of Cytochrome P450 and Associated Hydroxylation Reactions

Abstract: A review is made of the distribution and functions of cytochrome P450 in various tissues. ‘Normal’ levels of the enzyme are tabulated and factors inducing higher levels are discussed. Evidence suggestive of the existence of different species of the enzyme is discussed, as is the hypothesis that genetically defective (or absent) isoenzymes of cytochrome P450 can provide an explanation for the clinical findings caused by the adrenogenital syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 98 publications
(183 reference statements)
0
7
0
Order By: Relevance
“…Such variations in biological sensitivity to and metabolism of host terpenes by bark beetles indicate the involvement of the microsomal mixedfunction oxidases. Differences in enzymatic substrate affinities and rates of activity as well as differences between animal species in enzyme levels in the microsomes are well documented (HODGSON 1974; HODGSON and KULKARNI 1974;WICKRAMASINGHE 1975;KULKARNI et al 1976). The termimal oxidase of the NADPH-dependent microsomal system is cytochrome P-450, which is especially responsive to environmental and internal factors.…”
Section: Phylogenetic Importance Of Pheromone Productionmentioning
confidence: 99%
“…Such variations in biological sensitivity to and metabolism of host terpenes by bark beetles indicate the involvement of the microsomal mixedfunction oxidases. Differences in enzymatic substrate affinities and rates of activity as well as differences between animal species in enzyme levels in the microsomes are well documented (HODGSON 1974; HODGSON and KULKARNI 1974;WICKRAMASINGHE 1975;KULKARNI et al 1976). The termimal oxidase of the NADPH-dependent microsomal system is cytochrome P-450, which is especially responsive to environmental and internal factors.…”
Section: Phylogenetic Importance Of Pheromone Productionmentioning
confidence: 99%
“…[33][34][35] It has been reported that oxidative stress play a significant positive effects on the growth and progression of RCC. [36][37][38][39] Strong anti-oxidants are reported to have strong anticancer abilities. [40] Moreover, agents that causes reduction in anti-oxidative enzymes are reported to have significant effects on tumor progression markers.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress not only causes direct and irreversible oxidative damage to macromolecules but also disrupts key redox-dependent signaling processes. Reactive oxygen species include hydrogen peroxide (H 2 O 2 ), hydroxyl radical (OH -), peroxynitrite (ONOO -), and superoxide (O 2 −), many of which have been detected in renal cell carcinoma (Wickramasinghe, 1975;Block et al, 2007Block et al, , 2010. Intracellular generation of the superoxide anion O 2…”
Section: Sources Of Oxidative Stress In Renal Cancermentioning
confidence: 99%